Synthesis of Some Oxadiazole Derivatives as New Anticandidal Agents - Zafer Asim Kaplancikli (Molecules, 2011)
In this study, 5-[(pyrimidin-2-ylthio)methyl]-1,3,4-oxadiazole-2(3H)-thione (3) was synthesized via the ring closure reaction of 2-(pyrimidin-2-ylthio)acetohydrazide (2) with carbon disulphide. New oxadiazole derivatives 4a-f were obtained by the nucleophilic substitution reaction of compound 3 with various phenacyl bromides. The chemical structures of the compounds were elucidated by IR, 1H-NMR, 13C-NMR and FAB+-MS spectral data and elemental analyses. The newly synthesized derivatives 4a-f were tested in vitro by using a microbroth dilution method against C. albicans (clinical isolate, Osmangazi University, Faculty of Medicine, Eskişehir, Turkey), C. albicans (ATCC 90028), C. glabrata (clinical isolate, Osmangazi University, Faculty of Medicine, Eskişehir, Turkey), C. tropicalis (NRRL Y-12968), C. krusei (NRRL Y-7179), C. parapsilosis (NRRL Y- 12696), C. albicans (NRRL Y-12983), C. glabrata (clinical isolate, Anadolu University, Faculty of Science, Department of Biology, Eskişehir, Turkey). Among these compounds, compound 4a was found to be the most potent derivative (MIC = 0.007–0.06 versus ketoconazole: 0.001–0.007 mg/mL) against Candida species, except C. tropicalis and C. krusei when compared with the standard antifungal ketoconazole.